Nucleotide Analogue-Related Proximal Renal Tubular Dysfunction during Long-Term Treatment of Chronic Hepatitis B: A Cross-Sectional Study - Abhasnee Sobhonslidsuk; Jirachaya Wanichanuwat; Pawin Numthavaj; Areepan Sophonsritsuk; Supanna Petraksa; Alongkorn Pugasub; Paisan Jittorntam; Anucha Kongsomgan; Sittiruk Roytrakul; Bunyong Phakdeekitcharoen (Gastroenterology Research and Practice)
Background. There have been few reports of nucleotide analogue-related renal tubular dysfunction (RTD) in CHB patients. We assessed the prevalence and presentation of nucleotide analogue-related proximal RTD. Methods. A cross-sectional study was performed in CHB patients taking nucleotide analogues. Inclusion criteria were patients who were on adefovir or tenofovir as mono- or add-on therapy with lamivudine (LAM) >1 year. Serum and urine were collected. Fractional excretion of phosphate (FEPO4), uric acid (FEUA), and potassium was calculated. Renal losses were defined based on the criteria: protein (24-hour urine protein >150 mg), glucose (glycosuria with normoglycemia), phosphate (FEPO4 >18%), uric acid (FEUA >15%), potassium (renal potassium losses with hypokalemia), and bicarbonate (normal gap acidosis). Subclinical and overt proximal RTD were defined when 2 and ≥3 criteria presented. Results. Ninety-two patients were enrolled. The mean duration of nucleotide analogue taking was 55.1±29.6 months. Proximal RTD was found in 24 (26.1%) patients (subclinical 15 (16.3%) and overt 9 (9.8%)). The severity of RTD was associated with the duration of nucleotide analogue (P=0.01). Conclusions. The prevalence of proximal RTD in CHB patients taking nucleotide analogues was 26%. The severity of RTD was associated with the treatment duration. Comprehensive testing is necessary for early detecting nucleotide analogue-related nephrotoxicity.